Identification of undecylenic acid as EAG channel inhibitor using surface plasmon resonance-based screen of KCNH channels - Ze-Jun Wang; Purushottam B. Tiwari; Aykut Üren; Tinatin I. Brelidze (BMC, 2019)
Abstract Background KCNH family of potassium channels is responsible for diverse physiological functions ranging from the regulation of neuronal excitability and cardiac contraction to the regulation of cancer progression. KCNH channels contain a Per-Arn-Sim (PAS) domain in their N-terminal and cyclic nucleotide-binding homology (CNBH) domain in their C-terminal regions. These intracellular domains shape the function of KCNH channels and are important targets for drug development. Methods Here we describe a surface plasmon resonance (SPR)-based screening method aimed in identifying small molecule binders of PAS and CNBH domains for three KCNH channel subfamilies: ether-à-go-go (EAG), EAG-related gene (ERG), and EAG-like K+ (ELK). The method involves purification of the PAS and CNBH domains, immobilization of the purified domains on the SPR senor chip and screening small molecules in a chemical library for binding to the immobilized domains using changes in the SPR response as a reporter of the binding. The advantages of this method include low quantity of purified PAS and CNBH domains necessary for the implementation of the screen, direct assessment of the small molecule binding to the PAS and CNBH domains and easiness of assessing KCNH subfamily specificity of the small molecule binders. Results Using the SPR-based method we screened the Spectrum Collection Library of 2560 compounds against the PAS and CNBH domains of the three KCNH channel subfamilies and identified a pool of small molecules that bind to the PAS or CNBH domains. To further evaluate the effectiveness of the screen we tested the functional effect of one of the identified mEAG PAS domain specific small molecule binders on currents recorded from EAG channels. Undecylenic acid inhibited currents recorded from EAG channels in a concentration-dependent manner with IC50 of ~ 1 μM. Conclusion Our results show that the SPR-based method is well suited for identifying small molecule binders of KCNH channels and can facilitate drug discovery for other ion channels as well.